The O'Sullivan twins - Blyton, Enid. (b, 2013)
The "Stuck-Up" twins are determined that they will not be snowed by the climate at St. Clares - but are proved wrong. They realise that they are at the finest school in England and soon shape up, after some good talking-to's, a midnight feast, and various hi-jinks.
Keywords: St Clare's (Imaginary place) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Boarding schools